(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
Traffi cking in women for sexual purposes is part of the world reality. Knowing its causes, ways of action and the applicable legislation favors the fi ght against organized crime, while at the same time minimizing its effects, with the purpose of recovering and preserving human dignity.